Faith Informing Competitive Youth Athletes in Christian Schooling. Issue 3 (1st September 2016) - Hoven, Matt
ABSTRACT: How do students use religious faith to inform their actions in competitive sport? This qualitative study critically reflects on this question based upon the thinking processes and experiences of 15-year-old participants in sports and, in turn, produces a basic conceptual framework toward the question at hand. Overall, students reported a complex, competitive environment where they integrate, overlook, and avoid their faith as a means to inform their competitive drive in sport. Despite these mixed results and the dangers of aggressive sport, this paper concludes that Christian schools would be unwise to restrict support to only angelic sporting events and instead should, among several suggestions, incorporate insight from health standards, reconsider the use of prayer, and think about improved educational prescriptions.